Insight into uniform filming of LiF‐rich interphase via synergistic adsorption for high‐performance lithium metal anode - Yufang He; Li Wang; Aiping Wang; Bo Zhang; Hiep Pham; Jonghyun Park; Xiangming He (Exploration, 2024)
Abstract Multi‐scale simulation is an important basis for constructing digital batteries to improve battery design and application. LiF‐rich solid electrolyte interphase (SEI) is experimentally proven to be crucial for the electrochemical performance of lithium metal batteries. However, the LiF‐rich SEI is sensitive to various electrolyte formulas and the fundamental mechanism is still unclear. Herein, the structure and formation mechanism of LiF‐rich SEI in different electrolyte formulas have been reviewed. On this basis, it further discussed the possible filming mechanism of LiF‐rich SEI determined by the initial adsorption of the electrolyte‐derived species on the lithium metal anode (LMA). It proposed that individual LiF species follow the Volmer–Weber mode of film growth due to its poor wettability on LMA. Whereas, the synergistic adsorption of additive‐derived species with LiF promotes the Frank‐Vander Merwe mode of film growth, resulting in uniform LiF deposition on the LMA surface. This perspective provides new insight into the correlation between high LiF content, wettability of LiF, and highperformance of uniform LiF‐rich SEI. It disclosed the importance of additive assistant synergistic adsorption on the uniform growth of LiF‐rich SEI, contributing to the reasonable design of electrolyte formulas and high‐performance LMA, and enlightening the way for multi‐scale simulation of SEI.